2016
DOI: 10.1002/hbm.23246
|View full text |Cite
|
Sign up to set email alerts
|

Training your brain to be more creative: brain functional and structural changes induced by divergent thinking training

Abstract: Creativity is commonly defined as the ability to produce something both novel and useful. Stimulating creativity has great significance for both individual success and social improvement. Although increasing creative capacity has been confirmed to be possible and effective at the behavioral level, few longitudinal studies have examined the extent to which the brain function and structure underlying creativity are plastic. A cognitive stimulation (20 sessions) method was used in the present study to train subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 73 publications
4
58
0
Order By: Relevance
“…The AI also responds during action selection during decision-making (Paulus and Stein, 2006), and is therefore an integral component of cognitive control and the SN. Furthermore, the dACC has separately been implicated in cognitive regulation (Delevich et al, 2015), divergent thinking, error detection and response selection (Abraham et al, 2012; Sun et al, 2016). The dlPFC has extensive projections to striatal nuclei and is involved in top-down modulation of goal-directed behavior (Furman et al, 2011).…”
Section: Anatomy and Function Of The Sn Cortico-striatal Loopmentioning
confidence: 99%
“…The AI also responds during action selection during decision-making (Paulus and Stein, 2006), and is therefore an integral component of cognitive control and the SN. Furthermore, the dACC has separately been implicated in cognitive regulation (Delevich et al, 2015), divergent thinking, error detection and response selection (Abraham et al, 2012; Sun et al, 2016). The dlPFC has extensive projections to striatal nuclei and is involved in top-down modulation of goal-directed behavior (Furman et al, 2011).…”
Section: Anatomy and Function Of The Sn Cortico-striatal Loopmentioning
confidence: 99%
“…The reproducibility and relative ease of image acquisition has made these resting state networks an ideal focus of neuroimaging studies. Therefore, many studies implement resting state designs to study neuroplasticity as it pertains to training and development (Klados, Styliadis, Frantzidis, Paraskevopoulos, & Bamidis, ; Klein, Liem, Hanggi, Elmer, & Jancke, ; Smit, de Geus, Boersma, Boomsma, & Stam, ; Sun et al., ; Yoo, Sohn, & Jeong, ). In our study, we propose that lifelong training in the game of “Go” results in increased resting state connectivity to regions of the brain that are necessary for high‐level performance in board game playing.…”
Section: Discussionmentioning
confidence: 99%
“…This is described in Hebbian theory, which hypothesizes that neurons that co-activate during a task develop connections among one another (Brown & Milner, 2003;Favero, Cangiano, & Busetto, 2014). Therefore, repeated experiences or training will result in the formation of connections or networks in the brain that are specialized for a certain task or can be used to facilitate similar tasks (Chavan, Mouthon, Draganski, van der Zwaag, & Spierer, 2015;Debowska et al, 2016;Fink et al, 2015;Sun et al, 2016;Zhang, Yao, Shen, Yang, & Zhao, 2015). Expertise indicates expert skill or knowledge in a given field of study or profession.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was found that 5-MeO-matches the σ1 receptor which regulates cytoskeletal dendritic spine morphology and neurite outgrowth (Dakic et al, 2017). Therefore, σ1 receptor agonism may mediate neuroplastic processes which are crucial for creativity, cognitive flexibility, and sustained cognitive/behavioural changes (Sun et al, 2016). In addition, agonism of the σ1 receptor has been shown to have anti-inflammatory effects (Szabo, 2015) which may positively influence various creativity related cognitive processes.…”
Section: -Meo-dmt: An Endogenous Catalyst For Creativitymentioning
confidence: 99%